2009
DOI: 10.4142/jvs.2009.10.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic examination of the carpal canal in dogs

Abstract: The aim of this study was to determine the course of the median nerve and its adjacent structures in the carpal canals of 8 healthy dogs by using high-frequency transducers. Before performing ultrasonography, the transverse and posteroanterior diameters as well as the perimeter of the carpus were measured at just proximal to the side of the carpal pad. The anatomical structures were then determined at two levels of the carpal canal, which were named the proximal and distal levels, on the transverse sonograms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…On the other hand, Evans and de Lahunta [ 9 ] described that the canalis carpi has a wider extent, being the space generated deep to the flexor retinaculum and occupied by the tendons of the flexor carpi radialis , flexor digitorum superficialis , and flexor digitorum profundus muscles, the nervus medianus , the arteria and vena mediana , and the arteria and nervus ulnaris . This was also supported by Turan et al [ 10 , 11 , 12 ] in later studies about the diagnosis of potential carpal canal syndrome in dogs. Ettema et al [ 13 ], however, stated that the tendon of the flexor digitorum superficialis muscle is not located inside the canalis carpi .…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…On the other hand, Evans and de Lahunta [ 9 ] described that the canalis carpi has a wider extent, being the space generated deep to the flexor retinaculum and occupied by the tendons of the flexor carpi radialis , flexor digitorum superficialis , and flexor digitorum profundus muscles, the nervus medianus , the arteria and vena mediana , and the arteria and nervus ulnaris . This was also supported by Turan et al [ 10 , 11 , 12 ] in later studies about the diagnosis of potential carpal canal syndrome in dogs. Ettema et al [ 13 ], however, stated that the tendon of the flexor digitorum superficialis muscle is not located inside the canalis carpi .…”
Section: Introductionsupporting
confidence: 70%
“…The inconsistency found in the literature is probably related to the non-differentiation between the superficial and deep parts of the flexor retinaculum . Dyce et al [ 7 ], Evans and de Lahunta [ 9 ], and Turan et al [ 10 , 11 , 12 ] made their descriptions assuming that the flexor retinaculum was only constituted by the superficial part, which led to the inclusion of other tendons and neurovascular structures inside the hypothetical canalis carpi . However, the superficial part of the retinaculum did not generate a true canal below because, by definition, a canal is a tubular duct or channel.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nerves in humans have increased accumulations of connective tissue in areas of normal anatomic compression, and in a report on peripheral nerve compression secondary to lipomas in humans, the masses were found to be derived from the fatty tissues adjacent to the nerves (13,15). An ultrasonographic study of the canine carpal canal found a difference in echogenicity of the median nerve compared to other peripheral nerves, which the authors postulated as being secondary to an extra accumulation of connective tissue around the nerve (16). In this case, the CT showed the presence of normal adipose tissue in the carpal canal of the contralateral limb (ǠFig 1B).…”
Section: Discussionmentioning
confidence: 98%
“…The similarities demonstrated in our study suggest that it is possible to use the techniques of surgery and anaesthesia applied to the domestic dog [ 45 , 46 , 47 ]. The knowledge of the anatomy of nerves and muscle innervation is used in clinical diagnostics— for example, to differentiate injuries in the brachial plexus and around the periphery of the thoracic limb [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%